2019
DOI: 10.3390/plants8020038
|View full text |Cite
|
Sign up to set email alerts
|

Using Morphogenic Genes to Improve Recovery and Regeneration of Transgenic Plants

Abstract: Efficient transformation of numerous important crops remains a challenge, due predominantly to our inability to stimulate growth of transgenic cells capable of producing plants. For years, this difficulty has been partially addressed by tissue culture strategies that improve regeneration either through somatic embryogenesis or meristem formation. Identification of genes involved in these developmental processes, designated here as morphogenic genes, provides useful tools in transformation research. In species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 77 publications
2
95
0
Order By: Relevance
“…Even though there has been considerable progress enabling in vitro organogenesis and somatic embryogenesis in a variety of crops, transformation is often restricted to very few crop varieties, limiting the application of genome editing and transformation to crop improvement ( Altpeter et al., 2016 ). Expression of developmental genes to boost regeneration has been reported as promising strategy to overcome this hurdle in transformation of plants of agricultural interest ( Nagle et al., 2018 ; Gordon-Kamm et al., 2019 ). Here, we have discovered that the overexpression of the transcription factor GRF5 from Arabidopsis and/or its homologs increases transformation efficiency in sugar beet and maize.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though there has been considerable progress enabling in vitro organogenesis and somatic embryogenesis in a variety of crops, transformation is often restricted to very few crop varieties, limiting the application of genome editing and transformation to crop improvement ( Altpeter et al., 2016 ). Expression of developmental genes to boost regeneration has been reported as promising strategy to overcome this hurdle in transformation of plants of agricultural interest ( Nagle et al., 2018 ; Gordon-Kamm et al., 2019 ). Here, we have discovered that the overexpression of the transcription factor GRF5 from Arabidopsis and/or its homologs increases transformation efficiency in sugar beet and maize.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes encoding developmental regulators have been described to improve the regeneration efficiency in various plant species ( Heidmann et al., 2011 ; Horstman et al., 2017 ; Gordon-Kamm et al., 2019 ). For example, the constitutive expression of BABY BOOM ( BBM ), a transcription factor of the AP2/ERF family with diverse functions in plant development, can promote cell proliferation and ectopic embryo formation in cotyledons and leaves of Arabidopsis ( Boutilier et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify candidate TRA1 gene(s), first we looked for barley orthologs of genes already known to influence Agrobacteriummediated transformation. The ectopic over-expression of genes involved in cell growth and differentiation has been used to improve transformability in dicotyledonous species (reviewed in Gordon-Kamm et al, 2019) and in monocots (Lowe et al, 2016). In cereals, the over-expression of either of the genes WUSCHEL or BABY BOOM stimulates Agrobacterium-mediated transformation in maize, rice (Oryza sativa L.), sorghum (Sorghum bicolor L.) and sugarcane (Saccharum officinarum L.) (Lowe et al, 2016).…”
Section: Tra1 Candidate Genesmentioning
confidence: 99%
“…The GRF4-GIF1 technology results in fertile and normal transgenic plants without the need of specialized promoters or transgene excision, overcoming some of the limitations of transformation technologies with other morphogenic genes (Supplementary Table 8). Because GRF4-GIF1 likely operates at a later stage of meristem differentiation and stem cell proliferation 28 than Bbm-Wus2 [6][7][8] , there is potential to combine both technologies and have synergistic effects in the regeneration efficiency of recalcitrant genotypes. A concurrent and independent work showed that overexpression of Arabidopsis AtGRF5 and AtGRF5 homologs positively enhance regeneration and transformation in monocot and dicot species not tested here 34 .…”
Section: Disruption Of a Styi Restriction Sites Showed Cas9-induced Ementioning
confidence: 99%